An Ethics Framework for a Learning Health Care System: A Departure from Traditional Research Ethics and Clinical Ethics. (11th January 2013) - Faden, Ruth R.; Kass, Nancy E.; Goodman, Steven N.; Pronovost, Peter; Tunis, Sean; Beauchamp, Tom L.
Abstract: Calls are increasing for American health care to be organized as a learning health care system, defined by the Institute of Medicine as a health care system "in which knowledge generation is so embedded into the core of the practice of medicine that it is a natural outgrowth and product of the healthcare delivery process and leads to continual improvement in care." We applaud this conception, and in this paper, we put forward a new ethics framework for it. No such framework has previously been articulated. The goals of our framework are twofold: to support the transformation to a learning health care system and to help ensure that learning activities carried out within such a system are conducted in an ethically acceptable fashion .